2017
DOI: 10.1117/1.jmi.4.3.036001
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo tissue imaging for radiology–pathology correlation: a pilot study with a small bore 7-T MRI in a rare pigmented ganglioglioma exhibiting complex MR signal characteristics associated with melanin and hemosiderin

Abstract: , "Ex vivo tissue imaging for radiology-pathology correlation: a pilot study with a small bore 7-T MRI in a rare pigmented ganglioglioma exhibiting complex MR signal characteristics associated with melanin and hemosiderin," J. Med. Imag. 4(3), 036001 (2017), doi: 10.1117/1.JMI.4.3.036001. Abstract. To advance magnetic resonance imaging (MRI) technologies further for in vivo tissue characterization with histopathologic validation, we investigated the feasibility of ex vivo tissue imaging of a surgically removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this study, we also performed an ex vivo MR imaging on para n-embedded blocks from three subjects with minimal hemorrhage to allow comprehensive radiology-pathology correlation (32). Using a similar T2* relaxometry technique, several studies in preclinical tumor models demonstrated successful mapping of TAMs in treatment naïve tumors and in the context of immunotherapy (19,20,32,33). We also observed that R2* values correlated with both CD68 and CD86 positive cell counts in multiple ROIs randomly placed on areas of highly dense tumor and co-registered with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also performed an ex vivo MR imaging on para n-embedded blocks from three subjects with minimal hemorrhage to allow comprehensive radiology-pathology correlation (32). Using a similar T2* relaxometry technique, several studies in preclinical tumor models demonstrated successful mapping of TAMs in treatment naïve tumors and in the context of immunotherapy (19,20,32,33). We also observed that R2* values correlated with both CD68 and CD86 positive cell counts in multiple ROIs randomly placed on areas of highly dense tumor and co-registered with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…These observations could partly be attributed to the influence of temperature and relaxation rates on MRI imaging properties 21,22 . Other studies have also reported that MRI scanners and parameters used for in vivo imaging cannot be identically replicated while performing MRI in ex‐vivo studies 23–27 . Better MRI phantom models/in vivo studies using patients are warranted for the detection of the sensitivity of MRI in the detection of blood in body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported that MRI scanners and parameters used for in vivo imaging cannot be identically replicated while performing MRI in ex-vivo studies. [23][24][25][26][27] Better MRI phantom models/ in vivo studies using patients are warranted for the detection of the sensitivity of MRI in the detection of blood in body fluids. One of the limitations of the USG component of the study is that images were not scored multiple times by each radiologist, and hence, intraobserver variability could not be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the aim, MRI-microscopy datasets can vary along many axes: (1) whole brain ( Amunts et al., 2013 ) vs tissue blocks ( Gangolli et al., 2017 ), (2) serial histological sectioning ( Tullo et al., 2018 ) vs single-section sampling ( Meyer et al., 2006 ), (3) large ( Bagnato et al., 2018 ) vs small ( Meadowcroft et al., 2015 ) histology sections, (4) excised/biopsied tissue imaging ( Matsuda et al., 2017 ) vs post-mortem MRI ( Jonkman et al., 2019 ), and (5) the exact combination of MRI and microscopy modalities used. This diversity of the input data presents unique challenges ( Alyami et al., 2022 ) for the alignment of MRI-microscopy images (e.g., extreme contrast differences, vastly different spatial resolutions, 2D vs 3D image domains), which are difficult to overcome with existing registration software that was not optimised for this task.…”
Section: Introductionmentioning
confidence: 99%